1994
DOI: 10.1093/glycob/4.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Action pattern of polysaccharide lyases on glycosaminoglycans

Abstract: The action pattern of polysaccharide lyases on glycosaminoglycan substrates was examined using viscosimetric measurements and gradient polyacrylamide gel electrophoresis (PAGE). Heparin lyase I (heparinase, EC 4.2.2.7) and heparin lyase II (no EC number) both acted on heparin in a random endolytic fashion. Heparin lyase II showed an ideal endolytic action pattern on heparan sulphate, while heparin lyase I decreased the molecular weight of heparan sulphate more slowly. Heparin lyase III (heparitinase, EC 4.2.2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 0 publications
9
120
0
Order By: Relevance
“…This finding supports the evidence that CS B is present on versican, because chondroitinase ABC cleaves all types of CS chains, whereas chondroitinase ACII cleaves all CS chains except CS B (Ref. 44 and data not shown). The mAb 3-B-3, which recognizes stubs with the ⌬Di-6S terminal structure exposed by chondroitinase digestion (45), reacted strongly with chondroitinase ABC-treated versican, indicating that versican contains CS C as well.…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding supports the evidence that CS B is present on versican, because chondroitinase ABC cleaves all types of CS chains, whereas chondroitinase ACII cleaves all CS chains except CS B (Ref. 44 and data not shown). The mAb 3-B-3, which recognizes stubs with the ⌬Di-6S terminal structure exposed by chondroitinase digestion (45), reacted strongly with chondroitinase ABC-treated versican, indicating that versican contains CS C as well.…”
Section: Figsupporting
confidence: 89%
“…Because this enzyme selectively cleaves CS B (Ref. 44 and data not shown), this result indicated that versican contains CS B. This mAb also reacted with chondroitinase ABC-treated versican but not with chondroitinase ACII-treated versican.…”
Section: Figmentioning
confidence: 72%
“…Implications for Mode of Action-The structural differences between HL and CL may be correlated to their modes of action, as revealed by kinetic analysis with a variety of substrates (16,(71)(72)(73)76). As mentioned, biochemical data show that HL cleavage of HA, its primary substrate, proceeds via an initial endolytic cleavage, which is followed by rapid exolytic and processive activity, producing solely an unsaturated disaccharide unit as the end degradation product (3,15,27,28).…”
Section: Mechanism Of S Pneumoniae Hyaluronate Lyase Catalysis and Amentioning
confidence: 99%
“…Twisting motions between the two principal domains, revealed by simulated dynamics, also seem to play a role (15,19). Why, therefore, given the overall structural similarity of HL and CL (see Introduction), expected to lead to similar dynamic behavior (15,19,78), and the conserved hydrophobic interactions with substrate does CL not exhibit processive substrate cleavage (76)? One likely explanation lies in the added substrate bulk caused by sulfation of chondroitin.…”
Section: Mechanism Of S Pneumoniae Hyaluronate Lyase Catalysis and Amentioning
confidence: 99%
“…As heparitinase acts specifically on heparan sulphate (Jandik et al, 1994), this suggests that the active material is a species of heparan sulphate. As the purified material was protease treated before fractionation, and only minimal absorbance at 280 nm was observed around the active fractions, suggesting that little residual protein remained, the activity may lie in the carbohydrate moiety.…”
Section: +mentioning
confidence: 99%